Composition and magnetic properties of aluminium substituted yttrium iron garnet waste mill scales derived via mechanical alloying technique - Musa, Makiyyu Abdullahi; Azis, Raba'ah Syahidah; Hashim, Mansor; Osman, Nurul Huda; Adnan, Siti Irryani; Daud, Noruzaman; Mohd Shahrani, Nuraine Mariana; Sulaiman, Sakinah; Che Muda, Nor Nadhirah; Azizan, Abddul Halim (Malaysian Solid State Science and Technology Society, 2015)
This paper presents the effects of aluminium substitution on sample composition, density and magnetic properties of yttrium iron garnet, Y3Fe5O12 (YIG). Mill scales, in a form of flakes was obtained from the steel industry in Malaysia. The mill scales was purified to produce high purity hematite, Fe2O3. The mill scales derived Fe2O3 were used as raw material to prepare the aluminum substituted yttrium iron garnet Y3Fe(5-x) Al(x) O12 (Al-YIG) with variation compositional x = 0.0, 0.5, 1.0, 1.5 and 2.0 using mechanical alloying technique. X-ray fluorescence (XRF) was used to investigate the percentage compositions of the raw mill scales. The magnetic hysteresis of sample were investigate by using B-H tracer (MATS). Density of the Al-YIG bulk samples was found to decrease with increasing xAl2O3 content. The saturation magnetization Ms also shows a decrease with increase xAl2O3 content. The maximum saturation magnetization Ms and coercivity Hc was found at 310 G and 14.98 Oe, respectively. With increase xAl2O3 to 2.0%, the Ms and Hc were reduced to 29.35 G and 3.15 Oe, respectively.